Association between the ZJU index and gallstone prevalence in a Chinese adult population: a cross-sectional study - Teng, Yajie; Zhang, Daiyi; Chen, Yanjun; Qian, Lijuan; Xi, Qinhua (Frontiers in Medicine, 2025)
BackgroundGallstone disease is a major health concern, with various metabolic factors implicated in its pathogenesis. The ZJU index, a composite metabolic marker, has been suggested as a potential indicator of metabolic health. However, its association with gallstone disease in the Chinese population remains unclear. This study investigates the relationship between the ZJU index and gallstone prevalence through a cross-sectional analysis.MethodsWe included 55,241 individuals from a Chinese health screening cohort (January–December 2024). Descriptive statistics compared characteristics between individuals with and without gallstones. The ZJU index was calculated for each group, and its association with gallstone presence was assessed using multivariable logistic regression.ResultsAfter adjusting for confounding variables, a significant positive association was found between the ZJU index and gallstone prevalence (OR = 1.10, 95% CI: 1.04–1.16, p < 0.001). Stratified analyses revealed consistent associations in both men (OR = 1.10, 95% CI: 1.03–1.17, p = 0.005) and women (OR = 1.13, 95% CI: 1.02–1.25, p = 0.022). This positive association was further supported by smooth curve fitting. Formal threshold effect analysis did not identify a statistically significant inflection point (log-likelihood ratio p = 0.572), supporting a linear relationship across the range of ZJU index values.ConclusionThe ZJU index is positively associated with gallstone prevalence in the Chinese population. These findings highlight the potential of the ZJU index as a clinical marker associated with an increased risk for gallstone disease. However, given the cross-sectional nature of this study, causality cannot be inferred, and the observed relationship reflects a correlation rather than a direct cause-and-effect link.